Specification of the Archard’s wear model parameters for calculating wheels wear of freight cars with an axial load of 25 tons - A. V. Saidova; A. M. Orlova (Вестник Научно-исследовательского института железнодорожного транспорта, 2017)
The purpose of the study was a reasonable choice of the wear coefficient for the strong and weak stages in the Archard's abrasive wear model and the coefficient of friction on the flange and the rolling surface of the wheel for calculating the wear of the wheel profiles using dynamic models. 12-9853 universal gondola car with unloading hatches on three-element bogies of model 18-9855 was chosen as an object of research. At the first stage, the car wheels were measured (the thickness of the flange, quality of rolling) before and after the endurance running tests of the gondola car at the Test Loop of the JSC “VNIIZhT”. At the second stage in the “MEDYNA” software complex, a dynamic model of the car motion was developed, supplemented by the Archard model of wear. The effect of irregularities of the track on wear is determined under the conditions of the Test Loop and the value of the frictional force attributed to the contact area of the wheel with the rail is determined from the results of modeling the motion in tangent and curved sections of the track at which the transition from a weak wear stage to a strong one occurs. In the third part of the work, the hardness of the various areas of the surface of the worn wheel (4 samples) was measured in order to establish the ratio of the coefficient of friction on the flange and the surface of the wheel. In the final part, a multivariate calculation of the wear of the gondola wheels were carried out based on the results of which the wear curves of the rolling surface and the flange of the wheel were plotted on the coefficients of wear and friction between the wheel and the rail. This allowed choosing a pair of values ensuring the best convergence of the calculation results to the experimental results and, thus, to establish parameters of the Archard wear abrasive model for wheels with a hardened rolling surface. The specified parameters of the wear model can be used to develop new freight car bogies that provide a reduced wear of the wheel profiles, as well as to evaluate the influence of various factors on wheel wear in existing structures.